Factors enhancing implementation of occupational safety and health management systems in manufacturing industry of Mutare, Zimbabwe - Mandowa, Johanes; Matsa, Mark; Jerie, Steven (Frontiers in Public Health, 2025)
IntroductionSeveral studies elucidating a plethora of factors that influence establishment of OSH management systems in many industrial sectors have been conducted worldwide. Very few studies have been conducted to explicate factors influencing OSHMS implementation in Southern African countries, particularly in Zimbabwe. The study evaluated factors enhancing implementation of OSH management systems in the manufacturing industry of Mutare.MethodsA descriptive cross-sectional research design was utilized in the study. Primary data sources were questionnaires and interviews, and secondary data sources were e-OSH databases and past OSH research papers among others.ResultsThe results revealed the primary factors that enhance OSHMSs implementation as strong senior management commitment, involvement and support, strong employee involvement and participation, good safety culture, provision of adequate resources among others. Strong senior management commitment, involvement and support was identified as a catalyst of all other factors enhancing implementation of OSHMSs, hence a recommendation is made for employers to invest in programmes aimed at bolstering management commitment, involvement and support to OSH management.DiscussionConsidering that lack of adequate resources emerged as a significant impediment to OSHMS implementation, the study challenges the Government to take a leading role in establishing policies that unlocks various funding mechanisms to support workplaces in overcoming financial barriers in the implementation of OSHMSs. It can be inferred from the study results that employee involvement is central to effective implementation of OSHMSs as it enables the generation of knowledge, ideas and deployment of abilities that are paramount in enhancing OSH management. Inferential statistics also revealed the existence of an association between factory size and implementation of OSHMS. Development of scaled down OSHMSs requirements for small to medium manufacturing companies (SMMCs) is recommended considering the unattractiveness of OSHMSs in SMMCs owing to sustainability challenges. This recommendation places a demand on researchers and OSH stakeholders globally to rethink the current global order for OSHMSs implementation in order to advance an approach to OSHMSs implementation in the SMMCs that is sensitive to contextual compounding factors. The study develops a framework that is key in creating a “preventive safety culture” at workplaces which is an epitome for sustainability in OSHMSs implementation.